Pertussis vaccination in a cohort of older Australian adults following a cocooning vaccination program. Issue 29 (5th July 2018) - Dyda, A.; McIntyre, P.; Karki, S.; MacIntyre, C.R.; Newall, A.T.; Banks, E.; Kaldor, J.; Liu, B.
Abstract: Background: While recommendations to vaccinate adults against pertussis exist, information on uptake for adult tetanus-diphtheria-pertussis vaccine (Tdap) among older adults is limited. Methods: We used data from the 45 and Up Study, a prospective cohort of adults aged ≥45 years who completed a questionnaire between 2012 and 2014 asking about pertussis vaccination. We evaluated Tdap uptake following a program providing free vaccine for adults in contact with young children between 2009 and 2012. Results: Among 91, 432 adults (mean age = 66.3 years, SD = 9.6), 3.1% (n = 2823) reported receiving Tdap prior to the program. This increased seven-fold to 21.8% (n = 19898) after the program finished. Tdap coverage was almost twice as high in women compared to men and among adults more likely to be grandparents than those not. Conclusion: These findings suggest that funding for a targeted program can help to substantially increase vaccination coverage as well as decrease disparities in the uptake of Tdap in different sub-groups.